Direct Oral Anticoagulants and the Paradigm Shift in the Management of Venous Thromboembolism - Lim, Hui Yin; Nandurkar, Harshal; Ho, Prahlad (Seminars in Thrombosis and Hemostasis, 2018)
The advent of direct oral anticoagulants (DOACs) has revolutionized anticoagulation management in both stroke prevention and venous thromboembolism (VTE) treatment/prevention. Clinical trials and secondary real-world data have shown that DOACs have similar efficacy and, in some cases, improved bleeding safety profiles compared with vitamin K antagonists. Together with benefits of patient convenience, this has shifted the risk–benefit ratio toward long-term anticoagulation. However, current VTE risk assessment models are based on vitamin K antagonists and do not take into account the new paradigm of DOACs. Therefore, challenges to the thrombosis community remain to determine patients who would benefit from long-term anticoagulation in the DOAC era. Here, the authors review the current literature on risks and benefits of DOACs and their potential role in long-term VTE thromboprophylaxis as well as in current risk assessment models. The increasing use of DOACs, led by their convenience of use and generally lower bleeding rates, calls for a reevaluation of the current models as the benefits of long-term anticoagulation may begin to outweigh risks and inconvenience associated with their predecessors.
Keywords: direct oral anticoagulants; venous thromboembolism; thromboprophylaxis; DOAC